ANALYSIS OF SPERMATIDS MICRONUCLEI UNDER THE INFLUENCE OF ACRYLAMIDE - U. LAKSHMINARASAIAH; M. VENKATASWAMY; B. SUMAN; M. MEENA BAI; C. PALLAVI; G. SAILAJA; K. THYAGARAJU (The Bioscan, 2011)
The micronucleus test is an effective method for determination of the evolution of genotoxic or clastogenic agents of physical and chemical functions. The micronuclei are formed due to the condensation lagging off of acentric chromosomes, chromatid fragments or entire chromosomes and also due to non introduction of them in main daughter nuclei during metaphase or anaphase of cell division. Formation of micronuclei reflects chromosome damage and thus provide a marker for carcinogenesis analysis. Acrylamide is an important industrial chemical used in waste water treatment, adhesives and grout, cosmetics and also in laboratories. It is genotoxic, in in vitro and in vivo, in both somatic and germ cells. Acrylamide induces chromosomal aberrations, micronuclei formation, sister chromatid exchanges, SS-DNA breaks, polyploidy, aneuploidy and other mitotic disturbances, dominant lethal and specific locus mutations. Therefore a study was made on micronuclei assay to evaluate the degree of genotoxicity of acrylamide and its toxicologic effects on rat’s reproductive system after intraperitoneal injection of different doses of acrylamide. The Acrylamide treatment to rats caused damage not only to peripheral blood cells and reticulocytes but also to spermatids. The formation of micronuclei was evidence in our present study though acrylamide may not be used directly. The indirect consumption of acrylamide definitely causes damage to almost all type of cells in the rats.